Smart shopping assistant using mobile application development - Lok, Wai Loon (2025)
In the contemporary retail landscape, mobile applications have become indispensable tools for grocery shoppers. However, many existing platforms fail to offer a truly integrated and intelligent experience, lacking advanced features for personalized health-conscious decision-making, effortless list management, and practical in-store support. This project introduces the Smart Shopping Assistant, a cross-platform mobile application designed to address these limitations by creating a seamless, secure, and highly personalized shopping journey. The application is developed using the Flutter framework for broad device compatibility and is powered by Supabase for robust and secure backend services, including user authentication, data management, and PostGISbased geospatial queries. At its core, the assistant leverages a sophisticated AI engine, orchestrated through Dify and utilizing the Gemini API, to provide users with personalized nutritional analysis based on their specific health profiles. A key innovation is the on-device integration of Optical Character Recognition (OCR) via Google's ML Kit, which empowers users to instantly scan and digitize product nutrition tables for real-time evaluation. Furthermore, the inclusion of the Google Maps Service provides comprehensive location-based features, including nearby store discovery, address selection with autocompletion, and route visualization. Developed under an Agile methodology, the project prioritizes a user-centric design that blends convenience with valuable insights. By unifying an intelligent AI assistant, real-time nutritional data analysis via OCR, a full-featured e-commerce system with order management, and practical location-based services within a single platform, the Smart Shopping Assistant aims to empower consumers to make more informed, efficient, and health-aware purchasing decisions. This work contributes to the evolution of mobile commerce by delivering an integrated solution that enhances user trust, convenience, and dietary consciousness in everyday shopping.